The contribution of Poles to the development of medieval international law - Karska, Elżbieta (A thousand years of Poland's presence among the elite of European states, 2026)
When Poland became part of Western (Latin) civilization, Poles faced the necessity of organizing social life on the basis of the normative standards of conduct prevailing within that sphere. This was not merely a passive reception, but over time also an active co-creation of rules, including those governing relations between subjects of international relations. During the Middle Ages, many concepts were developed on Polish soil that contributed to the substance of international law, and in some cases even charted the course of its further development. These efforts were undertaken primarily in the context of the ongoing conflict between Poland and the Teutonic Knights. Polish scholars and diplomats, among them Stanisław of Skarbimierz and Paweł Włodkowic, argued in favor of concepts that — by limiting the right to resort to war — were defensible not only on ethical and moral grounds, but also from a legal standpoint. They were also consistent with Polish raison d'état. Their theses, addressing issues such as just war and religious tolerance, were formulated primarily on the basis of rules derived from Roman law and canon law, which at the time served as the prevailing standards of conduct within our civilizational sphere.